TUG1200 cnc lathe rebuilding. Setup of the new components in the machine - Kowalski, Tadeusz; Dubiel, Grzegorz (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2017)
Article covers topics dealing with possibility of rebuilding of the module-based machines. ModiÞ cation methods are presented in this paper. Moreover, increased functionality of rebuilt machines are described together with problems due to increased turning diameter and turning length, which requires modiÞ cation in lathe components. In addition, mounting issues of the new machine components are presented with additional accessories and components. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)